Integrating animal welfare into the WHO pandemic treaty: a thematic analysis of civil society perspectives and comparison with treaty drafting - Huang, Ying; Jiang, Shisong; Daminova, Nasiya; Kumah, Emmanuel (Frontiers in Veterinary Science, 2024)
The COVID-19 pandemic has exposed critical weaknesses in the global health system, highlighting the urgent need for a coordinated international approach to pandemic prevention and management. As negotiations for a new WHO pandemic treaty progress, the effective integration of animal welfare is crucial. This paper aims to investigate the perspectives of key civil society organizations on the integration of animal welfare provisions into the pandemic treaty. Through a thematic analysis of documents prepared by FOUR PAWS, Wildlife Conservation Society, and Action for Animal Health between 2020–2023, five major themes are identified: prevention of zoonotic spillover, One Health approach, animal health systems and infrastructure, sustainable and ethical animal management practices, and policy coherence and governance. A comparative analysis of these themes against the April 2024 draft of the pandemic treaty reveals areas of alignment and divergence. Due to the ongoing controversies and the need for further improvements, the WHO's intergovernmental negotiating body was unable to finalize the treaty text for the 77th World Health Assembly in May 2024, leading to an extended mandate until 2025. Based on the findings, the paper proposes recommendations to strengthen the integration of animal welfare into the treaty, arguing that incorporating these recommendations is critical for developing a transformative, equitable, and effective treaty that addresses the systemic drivers of pandemic risk.